Actual Tasks of Ensuring Harmony of Uzbek Philosophy and Development Strategy - Sharipov Abdukhakimjon Ziyoitdinovich (International Journal on Integrated Education, 2022)
This article analyzes the role of Uzbek national philosophy in the construction of New Uzbekistan, the foundation of the Third Renaissance, and the social-philosophical aspects of ensuring its connection and coordination with development strategies.